Impact of CYP2C19 and CYP2C9 gene polymorphisms on sodium valproate plasma concentration in patients with epilepsy. Issue 4 (31st August 2020) - Song, Cangsang; Li, Xingde; Mao, Panpan; Song, Wenbing; Liu, Lu; Zhang, Yang
Abstract : Background: Valproic acid (VPA) is a broad spectrum anticonvulsant drug, which could be partially metabolised by cytochrome P450 (CYP) 2C9 and 2C19 enzymes. This study was designed to investigate the relationship between CYP2C19 and CYP2C9 gene polymorphisms and the plasma concentrations of VPA in subjects with epilepsy. Methods: Eighty-three subjects with epilepsy aged 18–92 years were enrolled in this study. All were treated with sustained-release VPA monotherapy. Based on the genotypes of CYP2C19 and the ability to metabolise substrates, the subjects were divided into poor metabolisers, intermediate metabolisers and extensive metabolisers. Sanger sequencing was used to detect the genotypic and allelic frequencies of CYP2C19 (*1, *2 and *3) and CYP2C9 (*13) of the patients. Automatic immunity analysis was used to find steady-state trough plasma concentrations of VPA. By adjusting the plasma concentrations of VPA with body weight and total daily dose of VPA, the concentration-to-dose ratio of VPA (CDRV) was obtained. Data were analysed using SPSS software. Results: The genetic frequencies of CYP2C19*2, CYP2C19*3 and CYP2C9*13 were 33.1%, 3.0% and 5.4%, respectively, among patients with epilepsy from Yunnan province, China who used VPA therapy. The CDRV was significantly lower in the CYP2C19 extensive metabolisers (3.33±1.78) than it was in the CYP2C19 intermediate metabolisers (4.45±1.42) and the CYP2C19 poor metabolizers (6.64±1.06). The CYP2C19*2 and CYP2C19*3 alleles were correlated with the plasma VPA concentration, while the CYP2C9*13 allele had no effect on the plasma VPA concentration (p=0.809). Conclusions: The genetic polymorphisms of CYP2C19 significantly affect the VPA plasma concentration, and the dosage of VPA for intermediate and poor metabolisers could be lower than for extensive metabolisers. CYP2C9*13 carrier was not closely related to plasma concentrations of VPA in patients with epilepsy.